Participation in an Online Course about Death and Dying: Exploring Enrolment Motivations and Learning Goals of Health Care Workers - Claris Oh; Lauren Miller-Lewis; Jennifer Tieman (Education Sciences, 2020)
The Dying2Learn massive open online course (MOOC) was a five-week course designed for the general community covering various topics related to death and dying, developed with a sociocultural focus that encouraged personal reflection and open discussion, rather than a medical or clinical focus. Yet, the majority of the participants identified as health care workers. Their motivations to enrolling in the course as well as their learning goals were examined. Responses to questions relating to their motivations for enrolment and learning goals were assigned codes and grouped into themes. We then made comparisons between the different demographic and occupational groups. The most commonly mentioned responses related to general interest in the topic of death and dying. HCWs were more likely to mention work-related motivations and improving communication skills than non-HCWs. We found that HCWs hoped to be better at talking about death and dying, which might indicate a possible gap in their formal education in this area.